New polymorph of 1,3,5-triazine-2,4,6-triaminehexaacetic acid - Tapala W. (2014)
Single crystal of a new polymorph of 1,3,5- triazine-2,4,6- triaminehexaacetic acid has been growth and characterized. The structure of the title polymorph crystallized in the monoclinic space group C2/c with the unit cell parameters a = 20.443(4) Å, b = 10.5104(14) Å, c = 9.8022(11) Å, β = 118.212(6)°, V = 1855.9(5) Å 3, Z = 4, R = 0.112, Rw = 0.273 and S = 1.038. The principal feature of the new polymorph is characterized by a bundle of molecular columns each of which is built up of molecular units stacked along c in the offset face-to-face manner. Significance of hydrogen bonding interactions in regulating the assembly of molecules in the structure is then demonstrated. Detailed differences in molecular conformation, type and pattern of hydrogen bonding interactions are discussed and distinguished from the previous polymorph. The vibrational and electronic spectroscopic studies are included. © Springer Science+Business Media, LLC 2012.